The prevalence of cutaneous leishmaniasis in Bani Walid, Libya - Abdoarrahem, Mostafa M. O.; Ghana, Salah; Shaibi, Taher (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Cutaneous leishmaniasis is a parasitic disease causing skin lesions on infected person. CL isendemic in Libya including Bani Walid city, where this study was carried out to find the prevalence of the disease. Patients with cutaneous leishmaniasis attended to the health facilities, from May 2013 to October 2015, for medical help were investigated and demographic data was collected. The ratio of infection in Bani Walid appeared to be lower than previously reported in other Libyan municipalities. The year of 2013 included the highest number of cases with the peak of leishmaniasis in the period of July to October, whereas the year of 2015 showed fewer cases. However, the number of cases differed from month to another during the same year. The ratio of infection in males is higher than in females. The number of cases varied among sub-municipalities, Tarek Al-Mattar province formed almost the quarter.